Blood Pressure Response to Main Renal Artery and Combined Main Renal Artery Plus Branch Renal Denervation in Patients With Resistant Hypertension - Karl Fengler; Sebastian Ewen; Robert Höllriegel; Karl‐Philipp Rommel; Saaraaken Kulenthiran; Lucas Lauder; Bodo Cremers; Gerhard Schuler; Axel Linke; Michael Böhm; Felix Mahfoud; Philipp Lurz (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2017)
BackgroundSingle‐electrode ablation of the main renal artery for renal sympathetic denervation showed mixed blood pressure (BP)‐lowering effects. Further improvement of the technique seems crucial to optimize effectiveness of the procedure. Because sympathetic nerve fibers are closer to the lumen in the distal part of the renal artery, treatment of the distal main artery and its branches has been shown to reduce variability in treatment effects in preclinical studies and a recent randomized trial. Whether this optimized technique improves clinical outcomes remains uncertain. We report a 2‐center experience of main renal artery and combined main renal artery plus branches renal denervation in patients with resistant hypertension using a multielectrode catheter. Methods and ResultsTwenty‐five patients with therapy‐resistant hypertension underwent renal sympathetic denervation with combined main renal artery and renal branch ablation and were compared to matched controls undergoing an ablation of the main renal artery only. BP change was assessed by ambulatory measurement at baseline and after 3 months. At baseline, BP was balanced between the groups. After 3 months, BP changed significantly in the combined ablation group (systolic/diastolic 24‐hour mean and daytime mean BP −8.5±9.8/−7.0±10.7 and −9.4±9.8/−7.1±13.5 mm Hg, P<0.001/0.003 and <0.001/0.016, respectively), but not in patients with main artery treatment (−3.5±11.1/−2.0±7.6 and −2.8±10.9/−1.8±7.7 mm Hg, P=0.19/0.20 and 0.19/0.24, respectively). Systolic daytime BP was significantly more reduced in patients with combined ablation than in patients with main artery ablation (P=0.033). ConclusionsCombined ablation of the main renal artery and branches appears to improve BP‐lowering efficacy and should be further investigated.